Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To choose an equation that would be used to solve [tex]\(0 = -x^2 + 10x - 8\)[/tex], let us follow these steps:
1. Identify the type of equation:
The given equation [tex]\(0 = -x^2 + 10x - 8\)[/tex] is a quadratic equation. Quadratic equations often have solutions that can be expressed using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
2. Rewrite the equation in standard form:
The standard form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex]. For the given equation:
[tex]\[ -x^2 + 10x - 8 = 0 \][/tex]
Here, the coefficients are:
[tex]\[ a = -1, \quad b = 10, \quad c = -8 \][/tex]
3. Calculate the discriminant:
The discriminant [tex]\(\Delta\)[/tex] of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is calculated as:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
For the given coefficients:
[tex]\[ \Delta = 10^2 - 4 \cdot (-1) \cdot (-8) = 100 - 32 = 68 \][/tex]
4. Calculate the roots:
Using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substituting in the values:
[tex]\[ x = \frac{-10 \pm \sqrt{68}}{-2} \][/tex]
Simplifying further, we get two roots (solutions):
[tex]\[ x_1 = \frac{-10 + \sqrt{68}}{-2}, \quad x_2 = \frac{-10 - \sqrt{68}}{-2} \][/tex]
Simplifying these, we get:
[tex]\[ x_1 = 5 - \sqrt{17}, \quad x_2 = 5 + \sqrt{17} \][/tex]
5. Formulating the factorized form:
The roots [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex] can be used to generate the equation in the form [tex]\((x - x_1)(x - x_2) = 0\)[/tex]. Rewriting it:
[tex]\[ (x - (5 - \sqrt{17}))(x - (5 + \sqrt{17})) = 0 \][/tex]
6. Recognize the quadratic in vertex form:
With known roots, we can express the equation in vertex form, which looks like [tex]\((x - h)^2 = k\)[/tex].
The roots are symmetrically distributed around their average, which is the vertex:
[tex]\[ h = \frac{x_1 + x_2}{2} = \frac{(5 - \sqrt{17}) + (5 + \sqrt{17})}{2} = 5 \][/tex]
The constant term [tex]\(k\)[/tex] is derived from calculating:
[tex]\[ k = (x_1 - h)^2 = (x_2 - h)^2 = (\sqrt{17})^2 = 17 \][/tex]
Therefore, the correct equation that could be used to solve [tex]\(0 = -x^2 + 10x - 8\)[/tex] is:
[tex]\[ (x - 5)^2 = 17 \][/tex]
1. Identify the type of equation:
The given equation [tex]\(0 = -x^2 + 10x - 8\)[/tex] is a quadratic equation. Quadratic equations often have solutions that can be expressed using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
2. Rewrite the equation in standard form:
The standard form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex]. For the given equation:
[tex]\[ -x^2 + 10x - 8 = 0 \][/tex]
Here, the coefficients are:
[tex]\[ a = -1, \quad b = 10, \quad c = -8 \][/tex]
3. Calculate the discriminant:
The discriminant [tex]\(\Delta\)[/tex] of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is calculated as:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
For the given coefficients:
[tex]\[ \Delta = 10^2 - 4 \cdot (-1) \cdot (-8) = 100 - 32 = 68 \][/tex]
4. Calculate the roots:
Using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substituting in the values:
[tex]\[ x = \frac{-10 \pm \sqrt{68}}{-2} \][/tex]
Simplifying further, we get two roots (solutions):
[tex]\[ x_1 = \frac{-10 + \sqrt{68}}{-2}, \quad x_2 = \frac{-10 - \sqrt{68}}{-2} \][/tex]
Simplifying these, we get:
[tex]\[ x_1 = 5 - \sqrt{17}, \quad x_2 = 5 + \sqrt{17} \][/tex]
5. Formulating the factorized form:
The roots [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex] can be used to generate the equation in the form [tex]\((x - x_1)(x - x_2) = 0\)[/tex]. Rewriting it:
[tex]\[ (x - (5 - \sqrt{17}))(x - (5 + \sqrt{17})) = 0 \][/tex]
6. Recognize the quadratic in vertex form:
With known roots, we can express the equation in vertex form, which looks like [tex]\((x - h)^2 = k\)[/tex].
The roots are symmetrically distributed around their average, which is the vertex:
[tex]\[ h = \frac{x_1 + x_2}{2} = \frac{(5 - \sqrt{17}) + (5 + \sqrt{17})}{2} = 5 \][/tex]
The constant term [tex]\(k\)[/tex] is derived from calculating:
[tex]\[ k = (x_1 - h)^2 = (x_2 - h)^2 = (\sqrt{17})^2 = 17 \][/tex]
Therefore, the correct equation that could be used to solve [tex]\(0 = -x^2 + 10x - 8\)[/tex] is:
[tex]\[ (x - 5)^2 = 17 \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.